Необхідність запровадження судового прецеденту в Україні як результат зближення двох правових систем - Погребняк, О. С.; Pohrebniak, O. S. (Право і безпека. - 2013. - № 4 (51). - С. 14-19, 2013)
Розглянуто актуальну проблему необхідності введення судового прецеденту в Україні. Вказано основний принцип прецеденту. З’ясовано, в чому полягає обов’язок дотримання прецедентів судами. Відзначено, що правові системи романо-германського права та загального права мають взаємний вплив. Установлено, що дієвим механізмом забезпечення єдності і справедливості судової практики є судова практика Верховного Суду України, яку необхідно визнати джерелом права.

The paper focuses on a current problem concerning necessity of introducing a judicial precedent in Ukraine. The main principle of judicial precedent is indicated. It is examined how precedents constrain legal decision-makers. The authority of precedent is explained. It is investigated the principal requirement of the doctrine of precedent which is that courts respect earlier judicial decisions on materially identical facts. The doctrine also requires courts to depart from such decisions when following them would perpetuate legal error or injustice. When judges follow precedents they do so not because they fear the imposition of a sanction, but because precedentfollowing is regarded among them as correct practice, as a norm, deviation from which is likely to be viewed negatively. Precedents have authority for a variety of reasons. The most commonly cited reason is that to accept precedents as authoritative is to facilitate consistency and fairness in decision-making: when decision-makers treat precedents as constraints they increase the likelihood that similar cases will be treated alike. Another important explanation for the authority of judicial precedents is that they substantiate. A precedent might be followed if the ratio (general rule) guiding previous decision persuades decision-makers today, and therefore they may as well reapply it when required to decide on materially identical facts. The doctrine of precedent is not observed in Ukraine. It is noted that civil legal system and common law legal system have a great deal of mutual influence and in some areas convergence. The effective mechanism of fulfilling consistency and fairness in court decision-making in Ukraine is the judicial practice of the Supreme Court of Ukraine which should be recognized as the source of the law.

Рассмотрена актуальная проблема необходимости введения судебного прецедента в Украине. Указан основной принцип прецедента. Выяснено, в чём заключена обязанность соблюдения прецедентов судами. Отмечено, что правовые системы романо-германского права и общего права оказывают взаимное влияние. Установлено, что действенным механизмом обеспечения единства и справедливости судебной практики является судебная практика Верховного Суда Украины, которую необходимо признать источником права.
The necessity of introducing a judicial precedent in Ukraine as a result of legal systems’ convergence
Необходимость введения судебного прецедента в Украине как результат сближения двух правовых систем
Keywords: прецедент; правова система; судова практика; джерело права; precedent; legal system; court decision-making; source of the law; правовая система; судебная практика; источник права